2019
DOI: 10.1186/s13550-019-0523-8
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of [11C] choline and [18F] FET PET to detect glioma infiltration: a diagnostic accuracy study in eight patients

Abstract: Background Positron emission tomography (PET) is increasingly used to guide local treatment in glioma. The purpose of this study was a direct comparison of two potential tracers for detecting glioma infiltration, O-(2-[ 18 F]-fluoroethyl)- l -tyrosine ([ 18 F] FET) and [ 11 C] choline. Methods Eight consecutive patients with newly diagnosed diffuse glioma underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…(29) However, a key rationale for its use is the fact that FET and MET share the same uptake mechanism and a close correlation has been found between FET and MET uptake in primary brain tumors (e.g. gliomas and metastases), (22)(23)(24). Although FET and MET share the same molecular mechanism to enter the cell (via the L-type amino acid transporter 1 (LAT1)),( 21) in contrast to MET, FET is neither metabolized nor incorporated into proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(29) However, a key rationale for its use is the fact that FET and MET share the same uptake mechanism and a close correlation has been found between FET and MET uptake in primary brain tumors (e.g. gliomas and metastases), (22)(23)(24). Although FET and MET share the same molecular mechanism to enter the cell (via the L-type amino acid transporter 1 (LAT1)),( 21) in contrast to MET, FET is neither metabolized nor incorporated into proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative clinical studies have shown a strong correlation between FET and MET uptake in brain tumors (e.g. gliomas, metastases), (22)(23)(24) indicating that the utility of MET might be extrapolated to FET for patients with pituitary adenomas.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the extent of tumor remains delineated on MRI, with GTR defined by the T1-weighted contrast-enhanced regions for significant contrast-enhanced tumors [ 10 ]. However, biopsy-based studies indicated that tumor infiltrates beyond contrast enhancement [ 3 , 13 , 14 ], and a large-scale retrospective report suggested that the maximum resection of both contrast-enhanced and noncontrast-enhanced regions contributes to survival benefits in certain populations [ 15 ]. The identification of tumor infiltration beyond GTR is crucial for surgery, radiation planning and drug treatment [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…PET was performed 20 minutes after 18 F-FET injection. A recently published study from Amsterdam suggested that 18 F-FET/PET 60-90-min interval might have a higher diagnostic accuracy than the 20-40-min interval ( 22 ). Other authors have also reported better detection of diffuse glioma at intervals longer than 60 min compared with shorter intervals ( 23 ).…”
Section: Discussionmentioning
confidence: 99%